2019
DOI: 10.1111/jnu.12505
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Peripheral Venous Access in Children: An International Survey and Critical Appraisal of Assessment Tools and Escalation Pathways

Abstract: Background Peripheral venous cannulation is considered a routine procedure, yet 50% of first attempt insertions fail, necessitating repeat insertion attempts. Identification of children with difficult intravenous access (DIVA) can help promote prompt escalation to an appropriately skilled clinician. Objective To describe current international practice regarding the identification and management of children with DIVA, and to systematically review clinical tools and clinical pathways for children with DIVA. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
3
33
0
7
Order By: Relevance
“…This project co-produced and validated the DIVA Key instrument to support the assessment and subsequent escalation of PIVC insertion care in children with DIVA. Consistent with the evidence-base around DIVA risk factors and existing DIVA instruments [ 10 , 11 , 13 18 ], the DIVA Key included objective descriptions of vessel quality (e.g., appearance) and practice variables (e.g., acuity, previous access history). These indicators were uniquely complemented by rating the child’s reported or perceived anxiety, along with the clinician’s self-assessment of ability, and recommendations for management of procedural pain and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This project co-produced and validated the DIVA Key instrument to support the assessment and subsequent escalation of PIVC insertion care in children with DIVA. Consistent with the evidence-base around DIVA risk factors and existing DIVA instruments [ 10 , 11 , 13 18 ], the DIVA Key included objective descriptions of vessel quality (e.g., appearance) and practice variables (e.g., acuity, previous access history). These indicators were uniquely complemented by rating the child’s reported or perceived anxiety, along with the clinician’s self-assessment of ability, and recommendations for management of procedural pain and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Workshops were carefully planned using a scripted approach (example Supplementary material 1) and focused on joint decision-making between the research team, stakeholders, and consumers [ 28 ]. Workshop participants were provided an evidence summary (literature review findings [ 13 ]), excerpts from interview texts summarising desired instrument requirements, and an overview of current local DIVA policy. Expert opinion was an important consideration for co-production of instrument inclusions, with clinician gestalt linked with DIVA status prediction and first attempt insertion failure [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L a obtención de un acceso venoso periférico es un procedimiento de rutina que se realiza en los pacientes pediátricos que ingresan al hospital con el fin de administrar un tratamiento médico. Sin embargo, 50% de las veces la canulación de la vía venosa al primer intento es frustra, por lo que es necesario repetir la punción [1], [2], siendo necesario muchas veces el uso de punciones múltiples, resultando el procedimiento complejo, frustrante y todo un desafío para el personal médico y de enfermería [3].…”
Section: Definición Y Reconocimiento Del Problemaunclassified
“…There was a wide variation in practice as to how many total attempts the clinician performs before escalating to a central venous access device or alternative access. Similarly, Schults et al 14 recently reported only 16% of clinicians (n=23) globally used a DIVA scale, with resources used for the identification and escalation of children with DIVA are unstandardized or are inconsistently used. Further study is needed to streamline processes for DIVA identification and escalation to the appropriate clinicians, to improve patient safety and experience.…”
Section: Procedural Supportmentioning
confidence: 99%